2023
DOI: 10.1111/1365-2664.14411
|View full text |Cite
|
Sign up to set email alerts
|

A plea for scale, and why it matters for invasive species management, biodiversity and conservation

Abstract: Invasive species are suspected to be major contributors to biodiversity declines worldwide. Counterintuitively, however, invasive species effects are likely scale dependent and are hypothesized to be positively related to biodiversity at large spatial scales. Past studies investigating the effect of invasion on biodiversity have been mostly conducted at small scales (<100 m2) that cannot represent large dynamic landscapes by design. Therefore, replicated experimental evidence supporting a negative effect of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…While we identify the landscape scale as the focal unit for understanding and management, and communities and metacommunities as the concomitant level of organization, scale considerations remain central to both research and management for NPF-BI ( table 2 ). There is pervasive evidence for the scale-dependence of pattern and process in ecology broadly, but also in invasion ecology specifically [ 35 ]. Scale dependence is evident when detecting the effects of environmental filtering, competitive interactions [ 36 ], phylogenetic relatedness [ 37 ], and the relationship between species richness of native communities and invasion success [ 22 ].…”
Section: Insights For a Nature-positive Future With Biological Invasi...mentioning
confidence: 99%
See 1 more Smart Citation
“…While we identify the landscape scale as the focal unit for understanding and management, and communities and metacommunities as the concomitant level of organization, scale considerations remain central to both research and management for NPF-BI ( table 2 ). There is pervasive evidence for the scale-dependence of pattern and process in ecology broadly, but also in invasion ecology specifically [ 35 ]. Scale dependence is evident when detecting the effects of environmental filtering, competitive interactions [ 36 ], phylogenetic relatedness [ 37 ], and the relationship between species richness of native communities and invasion success [ 22 ].…”
Section: Insights For a Nature-positive Future With Biological Invasi...mentioning
confidence: 99%
“…The invasion process is also by definition a temporal one, including ongoing propagule pressure from the regional species pool. Time since invasion and community successional stages are therefore key considerations in decisions about invasion management ([ 35 ]; table 2 ).…”
Section: Insights For a Nature-positive Future With Biological Invasi...mentioning
confidence: 99%
“…For example, to calculate the average patch-scale L. cuneata abundance, we summed the L. cuneata abundance across all the plots in each patch and divided that value by the total number of plots sampled per patch (i.e., 168 plots patch −1 yr −2 ). Although scaling up our data from plot-level observations to larger spatial scales likely reduced our statistical power, significant observations at those scales are unlikely to be biologically meaningful and potentially more influenced by sheer sample size alone ( McMillan et al 2023 ). Our approach was to experimentally examine how our management approaches affected L. cuneata abundances at scales that are relevant to rangeland managers and producers in the tallgrass prairie.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…S1). A study of treatment effects at small scales (i.e., < 100 m 2 plots) where L. cuneata is homogenously distributed with high canopy cover does not, and cannot, represent the typical variability in L. cuneata cover across large landscapes ( McMillan et al 2023 ). While large-scale experiments with replicated landscapes such as our study often have substantially less statistical power compared with those at smaller scales, they are more relevant to boots-on-the-ground rangeland managers and producers.…”
Section: Lespedeza Cuneatamentioning
confidence: 99%
“…Previous studies have examined the spatial distribution of species on a large scale and their relationship to biodiversity conservation [15,[17][18][19][20]. These studies generally found a significant correlation between the diameter at breast height (DBH) and the age of individuals of the same species in the same living environment [21,22].…”
Section: Introductionmentioning
confidence: 99%